2005
DOI: 10.1196/annals.1327.017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rab18 and a New Golgin in the Secretory Pathway

Abstract: Two new amphibian genes have been isolated and characterized from frog melanotropes, and the level of expression of these genes is related to the secretory status of the cells. Both genes, Rab18 and a novel member of the golgin family of proteins, are ubiquitously expressed in endocrine and nonendocrine tissues, and their corresponding proteins appear to show intracellular distributions associated with discrete vesicular and tubular structures, respectively, suggesting that they may play relevant roles in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…storage melanotropes) presented higher Rab18 mRNA levels than those melanotropes displaying hypersecretory phenotype (i.e. secretory melanotropes) (19,20). In the present work, we have investigated Rab18 protein in these melanotrope subpopulations.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…storage melanotropes) presented higher Rab18 mRNA levels than those melanotropes displaying hypersecretory phenotype (i.e. secretory melanotropes) (19,20). In the present work, we have investigated Rab18 protein in these melanotrope subpopulations.…”
Section: Resultsmentioning
confidence: 94%
“…displaying high amount of a-MSH containing secretory granules but low secretory activity, both under basal conditions and in response to stimulatory factors) than in melanotrope cells displaying a secretory phenotype (i.e. with low intracellular a-MSH content but high basal secretory activity, and a strong secretory response to stimulatory secretagogues) (19,20). In the present work, we have furthered our study on the expression and subcellular localization of Rab18 in both endocrine and neuroendocrine cell types, and investigated its role in relation to the regulated secretory pathway.…”
mentioning
confidence: 99%
“…Rab18 has been localized to endosomes of mammalian cells by antibody staining in previous studies (Lutcke et al, 1994;Yu et al, 1993) and more recently to lipid droplets by multiple techniques including mass spectrometric analysis of purified lipid droplets (Brasaemle et al, 2004;Liu et al, 2004;Umlauf et al, 2004), immunofluorescence (Martin et al, 2005;Ozeki et al, 2005) and immunoelectron microscopy (Martin et al, 2005;Ozeki et al, 2005). Previous to this study, no fundamental generalized role has been proposed for Rab18 in the secretory pathway, although evidence has been provided for a role as a negative regulator of secretion in neuroendocrine cells (Malagon et al, 2005;Vazquez-Martinez et al, 2007).…”
Section: Role Of Rab18 In Golgi To Er Transportmentioning
confidence: 95%
“…In relation to the participation of Rab18 in the secretory pathway, a differential display analysis of genes expressed in pituitary melanotropes enabled us to isolate the RAB18 gene by virtue of its preferential expression in a subset of cells exhibiting low hormone secretory activity (Malagon et al, 2005). Further subcellular localization studies of Rab18 in (neuro)endocrine cells lines, such as the rat pheochromocytoma PC12 cell line, the adrenocorticotropin (ACTH)-secreting AtT20 cell line, and α-melanotropin stimulating hormone-producing melanotrope cells showed that this GTPase mainly distributed diffuse in the cytosol under non-stimulated conditions, whereas after specific stimulation of the cell secretory activity it colocalized with the secretory granule markers secretogranin II, chromogranin A, and NPY.…”
Section: Protein Structure Subcellular Localization and Function Of mentioning
confidence: 99%